A nationwide epidemiological and geodemographic analysis of lymphatic filariasis in Ecuador: a neglected and often forgotten disease in Ecuador - Izquierdo-Condoy, Juan S.; Naranjo-Lara, Patricio; Vásconez-Gonzalez, Jorge; Fernandez-Naranjo, Raul; Placencia-André, Romina; Davila, María G.; Carrington, Sarah J.; Ortiz-Prado, Esteban (Frontiers in Public Health, 2023)
Introduction: Lymphatic filariasis (LF) is a neglected parasitic disease transmitted by mosquitoes and affecting the lymphatic system. The aim of this study was to analyze the epidemiological and sociodemographic characteristics of patients with LF during the last 11 years of available data in Ecuador. Methods: A 11-year nationwide analysis of hospital admission and in-hospital mortality based on the National Institute of Statistics and Census (INEC) data was conducted in Ecuador from 2011-2021.The International Classification of Diseases 10th Revision (ICD-10) code for filariasis (ICD: B74) was used to retrieve information on severe LF as a proxy for incidence among 221 Ecuadorian cities. Results: A total of 26 hospital admissions and 3 deaths due to LF were registered. The highest mortality rate was found in populations over 80 years. Men accounted for 62.5% (n = 17) of total number of cases with an average incidence rate of 1.7 cases per / 1'000,000, while females accounted for 34.6% (n = 9), representing 1 case per / 1'000,000 woman. Cities located at lower altitude (459/1'000,000) reported higher incidence rates than those located at higher altitudes (7.4 / 1'000,000). Conclusions: This is the first study on LF in Ecuador. Although, Ecuador is not considered endemic for LF, we found evidence of the presence of this disease in recent years. The implementation and improvement of an adequate integrated epidemiological surveillance system will allow early identification of cases and therefore their respective treatment.